BioPhy magazine based on a floating market for problem-solving skills and environmental awareness - Lutfiyanti Fitriah; Ita Ita (Intelektual Pustaka Media Utama, 2022)
This study aimed to describe the validity and effectiveness of the floating market-based BioPhy magazine to improve problem-solving skills and encourage students to conduct environmental awareness campaigns. This research was development research with Tessmer formative evaluation model. The field test subjects were 24 students who studied fluids in the Fundamental Physics Course in the 2021/2022 academic year. Data were obtained through validation sheets and problem-solving questions. Data were analyzed quantitatively and qualitatively. The results showed that the developed magazine was valid and effective in improving students' problem-solving skills with an N-gain score in the field trial of 0.96 with a high category and an effect size of 12.61 with a strong influence category. In addition, based on the different tests, it was known that there is a significant difference between problem-solving abilities before and after learning. The magazine also succeeded in encouraging students to campaign on environmental awareness, as shown in the environmental-themed posters they made and shared on social media. Thus, the developed magazine was valid and effective to improve problem-solving skills and encourage environmental awareness campaigns on fluids in the Fundamental Physics Course.